2015 International Conference on Futuristic Trends on Computational Analysis and Knowledge Management (ABLAZE) 2015
DOI: 10.1109/ablaze.2015.7154935
|View full text |Cite
|
Sign up to set email alerts
|

A software up-gradation model with testing effort and two types of imperfect debugging

Abstract: Recent advances in the software world have seen the rise of various Software Reliability Growth Models (SRGMs). These SRGMs take into account various factors and associate them to reliability to come out with a new approach. Some of them consider calendar time as the governing factor while others argued that effort based modeling is more towards reality. In the real industrial scenario, due to the ever growing demands of the customer and stiff contention in the market, developers generally prefer to release th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…OSS reliability tools have been compared and reviewed and the characteristics and applications have been summarized 52 . More work in multi‐release modelling of OSS has been put forth by the number of researchers 13‐21,23‐29,34,38,40,42,48 …”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…OSS reliability tools have been compared and reviewed and the characteristics and applications have been summarized 52 . More work in multi‐release modelling of OSS has been put forth by the number of researchers 13‐21,23‐29,34,38,40,42,48 …”
Section: Literature Reviewmentioning
confidence: 99%
“…52 More work in multi-release modelling of OSS has been put forth by the number of researchers. [13][14][15][16][17][18][19][20][21][23][24][25][26][27][28][29]34,38,40,42,48 Following research gaps have been observed in the literature:…”
Section: Literature Reviewmentioning
confidence: 99%
“…In all the above models, it has been assumed that detection of faults leads to immediate correction and as such detection and correction are taken as one step process. Then Singh et al (2014a, b) presented a unified multi-upgraded model for two-stage detection and correction where they have incorporated two types of imperfect debugging only, and Kapur et al (2015) extended it to incorporate testing effort and two types of imperfect debugging. Tickoo et al (2016) developed a two-dimensional multi-release framework considering single change point in each release.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Then, in Singh et al, a unified multi‐upgraded model for two‐stage detection and correction is proposed where they have incorporated two types of imperfect debugging. The model has been extended to incorporate testing effort along with imperfect debugging in Kapur et al In previous studies, multi‐release framework/models have been forwarded wherein two stage fault detection and correction processes have been considered. More of latest work in the field of multi‐release have been put forth by researchers in .…”
Section: Literature Surveymentioning
confidence: 99%